Analytical Evaluation of Indicators Affecting Credit Risk in Islamic and Conventional Banking; (with Emphasis on Good Governance Index) - somayeh Naserzadeh; Asghar Abolhasani Hastiani; Bita Shaygani; Samira Motaghi (تحقیقات مالی اسلامی (پیوسته))
Credit risk is one of the most important risks faced by the banking system. The purpose of this article is to analyze the factors affecting credit risk in Islamic and conventional banking. We examine the effect of capital adequacy ratio, net ratio of loans to total assets, logarithm of total assets, good governance index and GDP growth (in terms of economic growth) as variables affecting credit risk in Islamic and conventional banking (50 selected banks) using the minimum method of Panel Generalized Squares (FGLS) and in the period of 2012-2017 in 8 countries of the world. The results of the research show that in Islamic banking, there is a negative and significant relationship between credit risk and the indicators of the ratio of net loan to total assets, capital adequacy and total assets but a positive and significant relationship with the good governance index. Also, economic growth index has no significant relationship with Islamic banking risk. The results in conventional banking show that the variables of capital adequacy, total assets, economic growth and good governance index have a negative and significant relationship with credit risk in conventional banking. Also, there is no significant relationship between the ratio of net loans to total assets and the risk of conventional banks.